Couple Identity Gaps, the Management of Conflict, and Biological and Self-Reported Stress in Romantic Relationships. (1st July 2017) - Merrill, Anne F.; Afifi, Tamara D.
Abstract : This study investigates the role of couple identity gaps in romantic partners' communicative and physiological management of stress during a conflict-inducing discussion task. A total of 118 couples participated in a laboratory study in which they engaged in a conflict-inducing discussion. Perceptions of intra- and extrarelationship couple identity gaps were associated with greater self-reported anxiety and stress for men and greater negativity for women during the conversation. Extrarelationship identity gaps were also significantly associated with heightened cortisol and (salivary alpha-amylase) sAA reactivity and delayed recovery, especially for women. The study extends the research on couple identity by introducing the concept of identity gaps into relational contexts to help explain why couples vary in their ability to manage stress .